Implication of GIS Technology in Accident Research in Bangladesh - Goswami, Dilip; Morshed, Md Manjur; Hasan, Md Sazedul (Journal of Bangladesh Institute of Planners, 2015)
Road accident is a major cause of loss of lives and economy of Bangladesh. National highways of Bangladesh have been a virtual death trap. However, accidents are concentrated on a few locations, which means, improvement of the scenario is possible through accident counterstrike measures. This paper has used Hazardous Location Index analysis to identify accident-prone areas of Joydebpur-Jamuna Bridge National Highway (NH405). In doing so, it has identified that about 11.50% accidents occurred in only 2.63% of the total length of the highway (highly accident-prone), whereas 12.41% length of the highway is accident-prone location. About 15.04% length of the highway needs counterstrike measures against accidents through road safety programs. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 159-166